A Population Pharmacokinetic Model of Vonoprazan: Evaluating the Effects of Race, Disease Status, and Other Covariates on Exposure. (8th February 2022) - Scarpignato, Carmelo; Leifke, Eckhard; Smith, Neila; Mulford, Darcy J.; Lahu, Gezim; Facius, Axel; Howden, Colin W.
Abstract: Vonoprazan, a potassium‐competitive acid blocker, is under investigation in the United States and Europe for the treatment of erosive esophagitis and Helicobacter pylori infection. Population pharmacokinetic (popPK) analysis allows the identification of factors that could affect drug exposure in population subgroups. Here, we report a popPK model based on pooled data sets of available pharmacokinetic (PK) studies in healthy volunteers and patients with gastroesophageal reflux disease, including erosive esophagitis, from Asia and Europe. This model was used to evaluate the impact of different covariates, including race and disease status, on vonoprazan exposure. We analyzed PK data from 746 patients and 410 healthy volunteers from 15 clinical trials using a nonlinear mixed‐effects approach to develop the popPK model. Model development focused on characterizing and quantifying the effects of clinical covariates of race (Asian vs non‐Asian) and disease status (gastroesophageal reflux disease vs healthy volunteers) on vonoprazan exposure. Identified clinical covariates included fed/fasting status, race, sex, disease status, weight, serum creatinine, and age. The impact of variations in these clinical covariates on exposure to vonoprazan was smaller than the effect of halving or doubling the dose. PK parameters were similar in Asian and non‐Asian populations. Variations in weight, age, and race are not predicted to have a clinically relevant impact on vonoprazan exposure or safety and require no changes in vonoprazan dosing. The limited impact of race on exposure suggests that efficacy and safety data for vonoprazan in Asian populations are translatable to non‐Asian populations.